ChemInform Abstract: Palladium‐Catalyzed Enantioselective Allylic Substitution in the Presence of Monodentate Furanoside Phosphoramidites. Issue 29 (July 2015) - Majdecki, Maciej; Jurczak, Janusz; Bauer, Tomasz
Abstract A library of monodentate furanoside phosphoramidites is prepared and applied in the Pd‐catalyzed allylic alkylation and amination.